The Dark Side of Dendritic Cells: Development and Exploitation of Tolerogenic Activity That Favor Tumor Outgrowth and Immune Escape - Seliger, Barbara; Massa, Chiara (Frontiers in Immunology, 2013)
Dendritic cells (DC) play a central role in the regulation of the immune responses by providing the information needed to decide between tolerance, ignorance, or active responses. For this reason different therapies aim at manipulating DC to obtain the desired response, such as enhanced cell-mediated toxicity against tumor and infected cells or the induction of tolerance in autoimmunity and transplantation. In the last decade studies performed in these settings have started to identify (some) molecules/factors involved in the acquisition of a tolerogenic DC phenotype as well as the underlying mechanisms of their regulatory function on different immune cell populations.